STRATEGI PENGENALAN BAHASA INGGRIS ANAK USIA DINI - Fitriyani, Fitriyani; Na’imah, Na’imah (Bunayya, 2023)
Learning in the digital era now uses a lot of English, because the development of advanced times requires children to learn to recognize early English learning, therefore the a need for the right strategy to introduce English to early childhood. This research aims to find out strategies for introducing English to early childhood. The research method used qualitative through a descriptive approach. The research subjects were a class A group of 15 young children who were studied in Cilegon City. The data analysis technique uses the theory of Milles and Huberman. The results of the study revealed that Nurul Ikhlas 1). The method used is singing and playing, 2). The material taught according to the theme follows the policies of the school, and the media used varies but are usually educational game tools such as puzzles, meronce buttons, sticks, and others. Conclusion Nurul Ikhlas PAUD has increased, especially early vocabulary in early childhood but of course the role of the teacher and the right strategy to provide learning to improve children's English